Notebooks : selections from the A.M. Klein papers - Klein, A. M. (Abraham Moses), 1909-1972 (Klein, A. M. (Abraham Moses), 1909-1972. Works. 1983., 1994)
"Much of A.M. Klein's finest prose is to be found in the mass of uncompleted work that he abandoned at the time of his breakdown, and that became accessible only when his papers were deposited in the National Archives. Notebooks offers a generous selection of this work, revealing previously unsuspected facets of Klein's character and artistry." "The fiction, criticism, and memoirs collected here focus on Klein's exploration of the role of the artist. The works illuminate crucial periods of his career, especially the early 1940s, when he was transforming himself into a modernist, and the early 1950s, when he was struggling to overcome the misgivings about his art that were to lead to his final breakdown." "The semi-autobiographical text which Klein referred to as 'Raw Material' and the unfinished novel of prison life entitled 'Stranger and Afraid' cast a new light on Klein's often frustrating relationship with the Montreal Jewish community. In 'Marginalia' he discusses poetic form and technique and makes observations on the nature of poetry, thereby providing insights into his own concerns as a writer. In 'The Golem, ' a profoundly ambiguous treatment of the act of creation, a self-portrait emerges of a storyteller who has lost faith in the power and value of his story. The volume includes a critical introduction, which places the material in the context of Klein's other works, as well as textual and explanatory notes."--Jacket.